Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Pada CV Bintang Makmur Bekasi - Rifky Ferry Siswanto; Hasanuddin (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Influence of Leadership and Work Discipline on Employee Performance at CV. Bintang Makmur Bekasi.This research aims to find out how the relationship between the variables Leadership (X1) and Work Discipline (X2) influences the Employee Performance variable (Y) at CV Bintang Makmur Bekasi. Research data is data taken using a questionnaire distributed to CV Bintang Makmur Bekasi employees. The population in this study were 44 employees of CV Bintang Makmur Bekasi. Data analysis techniques Data using Descriptive Analysis, Validity Test, Reliability, Simple, Multiple Regression Analysis, Classical Assumption Test, t Test (Partial), F Test (Simultaneous), Correlation Coefficient and Determination. Data processing in research uses SPSS 29. Based on the results, simultaneous tests produce a significance value of 0.001 < 0.05, which means that leadership and work discipline influence employee performance. Furthermore, the results of the coefficient of determination show a figure of 0.885, so 88.5% of Leadership (X1) and Work Discipline (X2) influence Employee Performance (Y) at CV Bintang Makmur Bekasi, while the remaining 21.5% is influenced by intervening variables which Thus, it can be concluded that the first hypothesis (Ha1), second hypothesis (Ha2), and third hypothesis (Ha3) can be accepted.